A relational lifecycle model of the emergence of network capability in new ventures. (August 2018) - McGrath, Helen; O'Toole, Thomas; Marino, Lou; Sutton-Brady, Catherine
This article presents a relational lifecycle model of the emergence of network capability in new ventures. Network capability is defined as a strategic ability learned in interaction with business partners. We focus on the foundational phases and processes of the emergence of this dynamic capability. The lifecycle model comprises three phases that evolve over time in tandem with the level of network engagement. The qualitative study identifies five tipping points or critical changes that move new ventures between the lifecycle phases. Using a sample of new ventures in a longitudinal action research design, the article demonstrates how new ventures emerge in network capability through increasingly complex and multilayered engagement processes with business partners. The relational lifecycle model contributes to the literature on how network capability emerges over time through the dynamics of interaction between business partners as new venture networks evolve and change.